Creating an inclusive mall environment with the PRECEDE-PROCEED model: a living lab case study. Issue 21 (9th October 2017) - Ahmed, Sara; Swaine, Bonnie; Milot, Marc; Gaudet, Caroline; Poldma, Tiiu; Bartlett, Gillian; Mazer, Barbara; Le Dorze, Guylaine; Barbic, Skye; Rodriguez, Ana Maria; Lefebvre, Hélène; Archambault, Philippe; et al.
Abstract: Purpose: Although public environments provide opportunities for participation and social inclusion, they are not always inclusive spaces and may not accommodate the wide diversity of people. The Rehabilitation Living Lab in the Mall is a unique, interdisciplinary, and multi-sectoral research project with an aim to transform a shopping complex in Montreal, Canada, into an inclusive environment optimizing the participation and social inclusion of all people. Methods: The PRECEDE-PROCEDE Model (PPM), a community-oriented and participatory planning model, was applied as a framework. The PPM is comprised of nine steps divided between planning, implementation, and evaluation. Results: The PPM is well suited as a framework for the development of an inclusive mall. Its ecological approach considers the environment, as well as the social and individual factors relating to mall users' needs and expectations. Transforming a mall to be more inclusive is a complex process involving many stakeholders. The PPM allows the synthesis of several sources of information, as well as the identification and prioritization of key issues to address. The PPM also helps to frame and drive the implementation and evaluate the components of the project. Conclusion: This knowledge can help others interested in using the PPM to create similar enabling and inclusive environments world-wide. Implication for rehabilitation: While public environments provide opportunities for participation and social inclusion, they are not always inclusive spaces and may not accommodate the wide diversity of people. The PRECEDE PROCEDE Model (PPM) is well suited as a framework for the development, implementation, and evaluation of an inclusive mall. Environmental barriers can negatively impact the rehabilitation process by impeding the restoration and augmentation of function. Removing barriers to social participation and independent living by improving inclusivity in the mall and other environments positively impacts the lives of people with disabilities